ANALISA PERUBAHAN PEMBEBANAN TERHADAP ARUS EXITASI UNIT 1 PADA PT PLN (PERSERO) SEKTOR PEMBANGKITAN TELUK SIRIH - Sepannur Bandri; Zuriman Anthony; Rafika Andari (Department of Electrical Engineering, UNJANI, 2023)
Changes in the load of a generator are always changing according to the needs of community demand. On the generator side of the Teluk Sirih PLTU using charcoal brush media as a reinforcing field. Where excitation plays an important role providing DC current to the generator rotor to create an intersection of electromotive forces. Changes in generator load that are always changing can have an impact on damage to equipment such as generators, and excitation. Where on December 6, 2017 the excitation current reads low at 473.7 amperes directly proportional to the armature current of 1404.2 amperes, the resulting power will also be low at 13200000 watts and a frequency of 49.9 Hz, creating a magnetic flux of 0.125 Weber that is larger or feels heavy so that the generator rotation is low at 2999 rpm and vice versa. Therefore the role of excitation takes over in order to provide greater current so that the field strength is maintained stable. Increasing the excitation current (If) results in a greater induced electromotive force (Ea). This increase in Ea also impacts the terminal voltage (Vt), causing it to vary. This relationship demonstrates that higher excitation current leads to an increase in terminal voltage, which is essential for maintaining voltage stability. To stabilize the low terminal voltage resulting from load changes, it is necessary to amplify the field gain current. This can be achieved by increasing the excitation current on the synchronous generator rotor. Understanding the characteristics of the excitation system allows for minimizing and avoiding damage to the generator caused by both overexcitation and underexcitation, ensuring the maintenance of a stable terminal voltage.